Lawfare - Gándara Pizarro, Jaime Humberto; Gándara Pizarro, Fabián Humberto (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
The main purpose of this research is to contribute to the increasingly growing debate on the legal-political phenomenon called lawfare, with significant theoretical elements that enable both to recognize it and to distinguish it from other phenomena that bear similarity. In particular, the interest lies in analysing in depth the term, from its connection with the field of war at its start, its historical development, the transformation suffered by the term to house the products of the link between political power and the judicial power, until its constituent elements and their nature using methodological tools that allow to determine, from the discussion with the literature, whether or not there is a phenomenon that can be called lawfare.